2020
DOI: 10.1302/2046-3758.98.bjr-2019-0301.r1
|View full text |Cite
|
Sign up to set email alerts
|

Promising targets and drugs in rheumatoid arthritis

Abstract: Aims Rheumatoid arthritis (RA) is a systematic autoimmune disorder, characterized by synovial inflammation, bone and cartilage destruction, and disease involvement in multiple organs. Although numerous drugs are employed in RA treatment, some respond little and suffer from severe side effects. This study aimed to screen the candidate therapeutic targets and promising drugs in a novel method. Methods We developed a module-based and cumulatively scoring approach that is a deeper-layer application of weighted gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Our novel finding suggests a central role of KLHDC7B-DT in LN disease activity. The third lncRNA, FAM30A, has previously been detected to interact with hub genes in a WGCNA analysis of a rheumatoid arthritis study (59), with our study revealing a similar central role of FAM30A in LN for the first time. Lastly, MIR600HG has been shown in a recent study to be differentially expressed between SLE patients and HC (60).…”
Section: Discussionsupporting
confidence: 76%
“…Our novel finding suggests a central role of KLHDC7B-DT in LN disease activity. The third lncRNA, FAM30A, has previously been detected to interact with hub genes in a WGCNA analysis of a rheumatoid arthritis study (59), with our study revealing a similar central role of FAM30A in LN for the first time. Lastly, MIR600HG has been shown in a recent study to be differentially expressed between SLE patients and HC (60).…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have also shown a significant reduction in arthritis severity and migration of Th17 cells to joints following the use of monoclonal antibodies against CCR6 [ 55 ]. HLA-DPA1 was identified as a common drug target for both Sjogren's syndrome and multiple sclerosis in a previous study [ 56 ], while another study more directly by weighted gene co-expression network (WGCNA) and linkage map (CMap) of illustrating HLA-DPA1 as a drug target for RA [ 57 ]. HLA-DRB1 is a recognised susceptibility-associated gene [ 58 ] with the strongest association with autoantibody-positive RA [ 59 , 60 ] and the HLA-DRB1*13 allele was found to confer strong protection against RA [ 61 ], which is consistent with the results of this study.IFNGR2 is a known causally associated gene for RA [ 62 ] and has also been identified as a potential target for the autoimmune disease, psoriasis [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed transcripts were defined by the criteria of |log 2 (fold change)| > 1 (|log 2 FC| > 1) and FDR < 0.05 for mRNA and lncRNA, p -value < 0.05 for miRNA and circRNA, respectively. The expression of transcripts was visualized by the R package pheatmap (v1.0.12) ( Li et al, 2020 ). Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed by the R package clusterProfiler (v3.11) ( Yu et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%